SOLIDARITAS ANTARUMAT BERAGAMA DALAM TRADISI BARIKAN DI DESA MOJONGAPIT JOMBANG - Dinda Mirtanty; Agus Machfud Fauzi; Farid Pribadi (Prodi Sosiologi Agama FIS Universitas Islam Negeri Sumatera Utara, 2021)
This research is motivated by the exsistence of inter-religious solidarity in Mojongapit Village trought the Barikan Tradition. The barikan tradition is a tradition carried out before independence day with the core activity of tahlil, but interfaith communities participate in this activity, which is different from other village communities. Thus, the purpose of this research is to find out the form of community solidarity in the barikan tradition, the driving factor and the inhibiting factors for inter-religious solidarity in the barikan tradition. This research is classified using purposive sampling. This research will analyzed theoretically using the perspective of Emile Durkheim’s theory of social solidarity. The results showed that : first, the form of solidarity carried out was paying dues, donating basic necessities, donatig snack and drinks, donating boxed rice, donating energy to make rice cone and preparing for events, donating equipment and supplies, compiling event rundowns, and providing entertainment. Second, the driving factors for solidarity are internal encouragement, the influence of religion, village principles, and the ability of the village head to instill tolerance, while there are no inhibiting factors.